2021
DOI: 10.3390/en14092682
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Steel Slag Biochar for Ammonium Nitrogen Removal from Aqueous Solution

Abstract: In this study, magnetic steel slag biochar (MSSB) was synthesized from low-cost steel slag waste to investigate the effectiveness of steel slag biochar composite for NH4-N removal and magnetic properties in aqueous solution. The maximum adsorption capacity of NH4-N by MSSB was 4.366 mg/g according to the Langmuir model. The magnetic properties of MSSB indicated paramagnetic behavior and a saturation magnetic moment of 2.30 emu/g at 2 Tesla. The NH4-N adsorption process was well characterized by the pseudo-seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Kim et al synthesized magnetic biochar from steel slag waste and pine sawdust (MSSB) for efficient NH 4 -N removal in an aqueous phase. They found that NH 4 -N was adsorbed on the MSSB surface via co-precipitation of Mg(NH 4 )PO 4 from magnesium and phosphate in biochar suspension [21]. The experimental results showed that the adsorption capacities of NH 4 -N can be influenced by many parameters such as NH 4 -N concentration, the ratio of steel slag to pine sawdust, and pyrolysis temperature.…”
Section: Short Review Of the Contributions In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al synthesized magnetic biochar from steel slag waste and pine sawdust (MSSB) for efficient NH 4 -N removal in an aqueous phase. They found that NH 4 -N was adsorbed on the MSSB surface via co-precipitation of Mg(NH 4 )PO 4 from magnesium and phosphate in biochar suspension [21]. The experimental results showed that the adsorption capacities of NH 4 -N can be influenced by many parameters such as NH 4 -N concentration, the ratio of steel slag to pine sawdust, and pyrolysis temperature.…”
Section: Short Review Of the Contributions In This Issuementioning
confidence: 99%
“…Thus, this Special Issue aimed to collect the state-of-the-art for the advances in WWTPs fields. Indeed, the papers published in this Special Issue cover a broad range of important issues; biochar application for wastewater treatment [19][20][21], LCA and cost optimization studies of WWTPs [22][23][24], enhanced anaerobic digestion [25], MFC of swine wastewater [26,27], and removal of radioactive and pharmaceutical pollutants by chemical processes [28,29]. In the next section, we provide a brief review of the papers published, roughly classifying them according to the thematic areas mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The iron oxide in tailings cannot be effectively separated by magnetic separation, so that most of the tailing is only used in low value‐added industries, such as building materials, road materials, and fertilizer for agriculture purposes. [ 5–8 ] The iron oxide is not fully utilized, resulting in a waste of iron resources. Therefore, it is necessary to recover iron oxide in the tailings, which is conducive to the construction of a resource‐saving and eco‐friendly steel industry.…”
Section: Introductionmentioning
confidence: 99%